Implementasi Model Pembelajaran Berbasis Proyek Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa SD IT Plus Qurthuba - Riswana; R. Supardi; Waddi Fatimah; Jusmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the implementation of the project-based learning model can improve students' critical thinking skills at SD IT Plus Qurthuba. This study is a type of classroom action research (CAR). The type of approach used is a descriptive quantitative approach. The subjects in this study were all students of class IV C, with a total of 35 students. The instruments used in this study were observation sheets, tests and documentation. The data collection techniques used were observation sheets, documentation and tests. The data analysis techniques used were quantitative data analysis and qualitative data analysis. From the results of the analysis of teacher teaching activity observations in cycle I, students' critical thinking skills were in the poor category with a presentation of 46% and cycle II were in the good category with a percentage of 80%. In cycle I, 16 students completed the course (46%) and 19 students (54%) had not completed it. Then it increased again in cycle II, 28 students completed the course (80%) and 7 students with a percentage of 20% had not completed it. Because there was a significant increase in cycle II, it can be concluded that the cycle ended in cycle II and the use of project-based learning models can improve students' critical thinking skills, students are active in learning and students actively pay attention to teacher explanations during the learning process in the science subject of class IV C SD IT Plus Qurthuba.